Bacterial cellulose synthesized with apple pomace enhanced by ionic liquid pretreatment. Issue 4 (20th April 2020) - Zhang, Wen; Wang, Jian-Jun; Gao, Yuan; Zhang, Le-Le
Abstract: Apple pomace was explored as alternative feedstock for producing bacterial cellulose (BC) by Gluconacetobacter xylinus following a cellulase saccharification performed after pretreatment of 1-allyl-3-methylimidazolium chloride ([AMIM]Cl). The dissolving process of apple pomace cellulose was observed by polarized light microscopy (PLM). As FT-IR and XRD results demonstrated, the IL pretreatment proved to be a physical process and no changes in the crystalline structure occurred during the pretreatment. However, the SEM result showed that more fissures and breakages appeared on the surface of pomace microfibers after IL-pretreating, which increased the contact area with cellulase and improved the enzymatic hydrolysis efficiency. An enhancing effect on the BC yield has been observed, 27% higher yield of BC obtained from hydrolysate as compared to sucrose-based medium indicates efficiency of IL-treated apple pomace to serve as high quality feedstock in BC production.